HASIL ANALISIS TENDANGAN PENALTI ENGLISH PREMIER LEAGUE PADA MUSIM 2019/2020 - Alamsyah Dian Nugraha Al Kadri, - (2021)
This study aims to determine the main influence and interaction of situational (match location), individual (kicking foot, playing position), and performance factors (shot direction and goalkeeper action) on penalty kick results in the English Premier League. Data is collected from the English premier league website and TV replays over the course of the season (from 2019-2020). A total of 78 penalties were recorded and analyzed taking into account the three groups of variables above and their respective penalty results (goals, saves or misses). Analysis of the influence of these factors on penalty results reveals that penalty kicks saved are mentally improved during home games and shots are directed into the bottom zone of the goal, particularly into the bottom right corner zone of the goal (penalty taker's perspective). Based on the current findings, players in offensive positions tend to be better and more productive in scoring goals especially in attacking positions, and goalkeepers should be encouraged to wait longer in order to save the goal from goals by the attacker. Although the performance factor is the most decisive factor in determining the result of a penalty, situational factors such as the period of the match can also affect the success of a penalty kick. Keywords: Penalty Kick Results, Situational Factors, Performance, Individual